Análise da cobertura da rede de linhas do transporte coletivo urbano em São Carlos - Souza Filho, Elias Martins de (2018)
This research emphasizes the importance of public transportation on the life of users and on city operation. São Carlos’ network of public transport bus lines is the study object, and is run, at the moment, by Suzantur. Through the creation of a network line map of the city, it was possible to analyze the network functionality, disposure and, through the method of determining accessibility area bands around the lines as served areas, calculate the portion of municipal population served by it. The research showed results for São Carlos, and also the possibility of applying this method on other cities. Although existing some overlapping lines, what may decrease the transportation efficiency, the study showed a positive result, as it revealed, for the last few years, an increase on the analyzed system’s coverage, going to 97,40% of the municipal population having accessibility categorized as “good”, which means, at this case, all people inside an area of a 200 meter band around the lines.